If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -1y)(4x + -1y) = 0 Multiply (3x + -1y) * (4x + -1y) (3x * (4x + -1y) + -1y * (4x + -1y)) = 0 ((4x * 3x + -1y * 3x) + -1y * (4x + -1y)) = 0 Reorder the terms: ((-3xy + 12x2) + -1y * (4x + -1y)) = 0 ((-3xy + 12x2) + -1y * (4x + -1y)) = 0 (-3xy + 12x2 + (4x * -1y + -1y * -1y)) = 0 (-3xy + 12x2 + (-4xy + 1y2)) = 0 Reorder the terms: (-3xy + -4xy + 12x2 + 1y2) = 0 Combine like terms: -3xy + -4xy = -7xy (-7xy + 12x2 + 1y2) = 0 Solving -7xy + 12x2 + 1y2 = 0 Solving for variable 'x'. Factor a trinomial. (3x + -1y)(4x + -1y) = 0Subproblem 1
Set the factor '(3x + -1y)' equal to zero and attempt to solve: Simplifying 3x + -1y = 0 Solving 3x + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 3x + -1y + y = 0 + y Combine like terms: -1y + y = 0 3x + 0 = 0 + y 3x = 0 + y Remove the zero: 3x = y Divide each side by '3'. x = 0.3333333333y Simplifying x = 0.3333333333ySubproblem 2
Set the factor '(4x + -1y)' equal to zero and attempt to solve: Simplifying 4x + -1y = 0 Solving 4x + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 4x + -1y + y = 0 + y Combine like terms: -1y + y = 0 4x + 0 = 0 + y 4x = 0 + y Remove the zero: 4x = y Divide each side by '4'. x = 0.25y Simplifying x = 0.25ySolution
x = {0.3333333333y, 0.25y}
| 4a+9=8a-18 | | 1x1/2 | | X(2x-1)(x-3)=o | | 5x+13=7x-11 | | -x-9-6x=-58 | | (2x+6)(3x-5)=(6x-1)(5+x) | | 1n(4x-9)=0 | | 2+9x-7x^2=0 | | -5x-9=27+x | | 31.4=3.14d | | (X-3)(x-5)=9(x-6) | | C=22/7*2*7 | | -x/3-25 | | 144/=y | | a+(a+6)=42 | | -2x-9-2x=-21 | | (-1/6)*(9/12) | | -6(-4n+5)=-20+24n | | 40+.45M=48.10 | | 0.05/0.5*0.5=x | | 0.05/0.5*0.5=? | | 0.05/0.5*0.5 | | 2X=108-x | | y+4+9=13 | | 6.7x+4=5.7x | | 4(x+2)-6(x-3)=16 | | 0.05/0.25 | | x+z=140 | | 9/12y=-1/6 | | 2(5x+1)+12=54 | | 5/; | | 10+8x=11-2(1-5x) |